Breast cancer in Sabah, Malaysia: a two year prospective study - Leong, B.D.K.; Chuah, J.A.; Kumar, V.M.; Yip, C.H. (West Asia Organization for Cancer Prevention, 2007)
Sabahan women with breast cancer present late. Great efforts are needed to improve public awareness of breast cancer, especially among those who have higher risk of presenting with advanced disease.